Statistical Approach to Alcoholysis Optimization of Sorrel (Hibiscus Sabdariffa) Seed Oil to Biodiesel and Emission Assessment of Its Blends - Betiku, Eriola; Adepoju, T.F.; Solomon, B.O. (Ife Journal of Technology, 2012)
In an effort to optimize the reaction conditions of biodiesel production from Sorrel seed oil, Response Surface Methodology (RSM) was applied and the effects of reaction temperature, catalyst amount, reaction time and methanol/oil molar ratio, and their reciprocal interactions were ascertained. A total of 30 experimental runs were designed by Central Composite Rotatable Design (CCRD) and carried out. A quadratic polynomial was obtained for predicting the transesterification process and the ANOVA test showed the model to be significant (p<0.05). The validity of the predicted model was established by carrying out three independent replicate experiments. The actual maximum Sorrel oil methyl ester (SOME) yield obtained was 99.23% (w/w) at methanol/oil molar ratio of 6.21, catalyst amount of 1.03 wt%, reaction temperature of 51 oC and reaction time of 63 min. The fuel properties of the SOME were found to be within the ASTM D6751 and DIN EN 14214 biodiesel standards. The fatty acid profile of the SOME revealed the dominant fatty acids were oleic (58.34%), palmitic (18.28%) and linoleic (21.19%). Emission assessment revealed 70% reduction of CO at B80 and 80% reduction of NO concentration at B40.